Philip's guide to seashells of the world A.P.H Oliver. - Oliver, A. P. H. (Richmond Hill, Ont; Buffalo, N.Y Firefly Books, 2004)
Identification guide to seashells with more than 1000 species illustrated
Keywords: Mollusques--Identification.; Shells--Identification.; Mollusks--Identification.; Coquillages--Identification.